Mobile application for animal classification using interactive multimedia / Khaleda Rafieka Khailmi - Khailmi, Khaleda Rafieka (2022)
Information technology's quick advancement has had an impact on many facets of society, including science education. However, traditional learning teaching strategies continue to employ in primary schools, particularly in the subject of science. Classification here is defined as the arrangement of objects such as organisms, ideas, or information into groups. Hence, this application entitled is Mobile Application for Animal Classification Using Interactive Multimedia designed and developed as a teaching and learning aid in learning Science Classification of Animal topic. The interaction design lifecycle model had been implemented in the development of this application. This educational tool is meant to support the learning and teaching processes through the use of diverse media, such as instructional video resources for elementary and primary school children. Multimedia components will increase learning interest, particularly for science subjects that call for reading, comprehension and memorization. The ADDIE model has different phases in development such as analysis, design, develop, implement, and finally evaluate. This mobile application evaluated with Expert Review by distributing questionnaires to one experts and including questions for 33 respondents from User Acceptance Test (UAT). The result of Expert Review shows that the Interactive Multimedia-Based Mobile Application is suitable to use but needs to be refined and improved. The results of the UAT showed that the mobile application in the context of Science education is generally efficient and helpful, especially for primary school students and teachers. In conclusion, the results indicate that the Interactive Multimedia-Based Mobile Application is interesting and valuable for students in improving subject science especially for animal classification, as it is an important part of the science learning.